ANALISIS FAKTOR OPERASIONAL TERHADAP KINERJA RUMAH SAKIT (Studi Kasus : Rumah Sakit Nasional Diponegoro) - Edward Pridolin Vivaldi Pakpahan; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2021)
This study aims to analyze the effect of operational factors on hospital performance and also analyze the relationship between BPJS patients and General patients at Diponegoro National Hospital. In this study, the operational factor tested was ALOS as an independent variable. And the performance of the hospitals tested is hospital costs that are influenced by ALOS as the dependent variable. The method of sampling in this study used the purpose sampling technique. The analysis technique used is multiple regression analysis.The results of this study indicate that the lower ALOS will produce efficient performance and lower costs. And ALOS BPJS and ALOS General have a positive effect on hospital performance. However, ALOS General is more efficient than ALOS BPJS. And the results of this study indicate that ALOS BPJS is different from ALOS General.